2017
DOI: 10.1016/j.jcyt.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of NF-κB sensing and interleukin-4 secreting mesenchymal stromal cells as an “on-demand” drug delivery system to modulate inflammation

Abstract: Chronic inflammation is associated with upregulation of the transcription factor NF-κB and excessive inflammatory cytokine secretion by M1 macrophages. The anti-inflammatory cytokine IL-4 converts pro-inflammatory M1 macrophages into an anti-inflammatory and tissue regenerative M2 phenotype, thus reducing inflammation and enhancing tissue regeneration. We have generated NF-κB responsive, or constitutively active IL4-expression lentiviral vectors transduced into murine bone marrow-derived mesenchymal stromal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 55 publications
2
87
0
Order By: Relevance
“…MSCs preconditioned by transient exposure to inflammatory cytokines alone or combined with PAMP enhanced immunomodulation and tissue regeneration (10)(11)(12). We recently observed that when MSCs were exposed to LPS repeatedly, NF-kB activation was significantly increased compared with single LPS exposure (13). A similar phenomenon of intermitted stimulus leading to dissimilar and nonstereotypical responses in innate immunity has been reported in studies conducted with macrophages exposed to PAMPs such as b-glucans and LPS and has been named "innate immune memory" or "trained immunity" (14)(15)(16).…”
mentioning
confidence: 99%
“…MSCs preconditioned by transient exposure to inflammatory cytokines alone or combined with PAMP enhanced immunomodulation and tissue regeneration (10)(11)(12). We recently observed that when MSCs were exposed to LPS repeatedly, NF-kB activation was significantly increased compared with single LPS exposure (13). A similar phenomenon of intermitted stimulus leading to dissimilar and nonstereotypical responses in innate immunity has been reported in studies conducted with macrophages exposed to PAMPs such as b-glucans and LPS and has been named "innate immune memory" or "trained immunity" (14)(15)(16).…”
mentioning
confidence: 99%
“…This simple procedure avoids the potential risk of genetic modification‐mediated cell transformation. In addition, the induction of osteogenesis in the preconditioned MSCs was found in vitro, which was not observed with IL4 secreting MSCs …”
Section: Discussionmentioning
confidence: 82%
“…In addition, the induction of osteogenesis in the preconditioned MSCs was found in vitro, 13 which was not observed with IL4 secreting MSCs. 14 In conclusion, NFκB-IL4 MSC has shown an "on-demand" immunomodulatory ability to mitigate the proinflammatory response and subsequent tissue damage. The therapeutic potential of NFκB-IL4 MSCs in periprosthetic osteolysis or other chronic inflammatory diseases will be further examined in translational in vivo models.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Modulation of M1 to M2 phenotype at an appropriate time optimized bone regeneration in vitro [3]. However, during the acute (as opposed to the chronic) inflammatory period of bone healing which lasts several days, IL-4 was shown to inhibit osteogenesis by MSCs [4,5]. A novel strategy of GM MSCs therapy to optimize bone regeneration and remodeling is continuous production of IL-4 by GM-MSCs together with a second growth factor to counteract the initial potential adverse effects of IL-4 during the first few days of inflammation.…”
Section: Introductionmentioning
confidence: 99%